Encephalopathy an Atypical Presentation of Intussusception: A Case Report - Venma Mampilly; Sasikumar Manalumukkil Sankaran; Ramaraj Subbiah (University Library System, University of Pittsburgh, 2020)
Background: Intussusception Encephalopathy is a pediatric emergency where a stuporous child presents with or without abdominal symptoms. Neurological manifestations of intussusception are an atypical presentation of this condition. It often misleads clinicians to other differential diagnoses of encephalopathy. The Case: We present to you a case of an 11-month-old child presented with encephalopathy, acute in onset with underlying intussusception. Conclusion: Intussusception encephalopathy is a pediatric emergency. It should be kept as a differential diagnosis when a child presents with complaints of acute onset of drowsiness with or without abdominal symptoms. Early diagnosis could save grave complications and improve the prognosis.